(3GdeYGT GdeHcQ ai GdbGfhf GdeUQi GdebGQf (B/ s - (3eMeO YHOGdYRjR eMeO TGgjfs; (3CMeO MSf GdHQY`i s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3GdCUd ai fXGe GdJCejf GdGLJeGYi gh JZWjI eNGWQ GdTjNhNI h GdYLR GdhaGI(B: (3h jSJMb eYGT GdTjNhNI YfO HdhZ GdeDef Ydjg Sf GdJbGYO(B: (3h jSJgOa JYhjV GdONd(B: (3h GYJHGQG ef (B1/4/1964 (3GSJMOK fXGe GdeYGT GdeHcQ GdPi jWdH UQag bHd Sf GdJbGYO(B: (3h bO befG HGdJYQa Ydi eaghe hCSHGH GdeYGT GdeHcQ(B: (3h Ydi GdQZe ef JONd GdeTQY GdeUQi CcKQ ef eQI HEUOGQ JYOjdGJ ddMO ef JRGjO CYOGO GdeYGT GdeHcQ HOGjI ef bGfhf (B130 (3dSfI (B2009 : (3h bGfhf (B120(3dSfI (B2014: (3GdG Cf GdJYOjdGJ de JKeQ Yf fJGFL EjLGHjI fMh JNajV eYOdGJ GdNQhL GdeHcQ GdCeQ GdPi MOG HGdeTQY Edi EUOGQ bGfhf (B148 (3dSfI (B2019: (3h befG HJbjje GdeYGT GdeHcQ ef fGMjg GdeRGjG h GdYjhH ai VhA BKGQg GdGbJUGOjI h GdGLJeGYjI(B: (3h YQV Cge GdJhUjGJ h GdebJQMGJ ai VhA bGfhf (B148 (3dSfI (B2019: (3GdPi hVnY oTQhWkG ef GdUYH JhGaQgG(B: (3h ef Gdeecf Cf fWdb YdjgG TQhWkG JYLjRjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdELJeGYjI, (B2022s
(3HHdjhLQGajG(B: (3UaMGJ (B294-309s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJCejf GdELJeGYis; (3bhGfjf GdJCejf GdGLJeGYj s; (3GdeYGT GdeHcQs; (3Sf GdJbGYOs; (3GdbGfhf GdeUQj GdebGQfs; (3bGfhf (B79 (3dSfI (B1975 s; (3CSHGH GdeYGT GdeHcQs; (3GdeYGT GdeHcQ aj aQfSGs; (3GdeYGT GdeHcQ aj Tjdj s; (3eRGjG hYjhH GdeYGT GdeHcQ s; (3UfGOjb GdJCejf GdGLJeGYj s; (3MGdGJ GdeYGT GdeHcQ s; (3GdbGfhf (B148 (3dSfI (B2019 s; (3bjeI GdeYGT GdeHcQ s; (3GdGSJOGeI GdeGdjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs